Unraveling enhanced brain delivery of paliperidone-loaded lipid nanoconstructs: pharmacokinetic, behavioral, biochemical, and histological aspects. (31st December 2022) - Rehman, Saleha; Nabi, Bushra; Javed, Amaan; Khan, Tahira; Iqubal, Ashif; Ansari, Mohammad Javed; Baboota, Sanjula; Ali, Javed
Abstract: Antipsychotics are accompanied by extrapyramidal side effects that deter treatment adherence and patient compliance. Paliperidone (PPD), an atypical (second-generation) antipsychotic recommended for managing schizophrenia presents biopharmaceutical challenges and pharmacological constraints which dissuade it from crossing the brain barrier. The present research aimed to assess paliperidone-loaded lipid nanoconstruct (PPD-LNC) for an improved antipsychotic activity for managing schizophrenia. High % cell viability in Neuro-2a cells (70–98%) exhibited the safety of PPD-LNC. The pharmacokinetic data showed a 3.46-fold improvement in the relative bioavailability in the brain for PPD-LNC compared to a drug suspension. The pharmacodynamic evaluation demonstrated a significant ( p < .05) reduction in cataleptic behavior, attenuated escape latency, and prolonged stay in the open arm with PPD-LNC, thus showing its effectiveness in reducing extrapyramidal symptoms. The histopathological images further validated the safety of the formulation. Reduction in NF-κB levels as identified by immunohistochemical analysis exhibited the anti-inflammatory effect of PPD-LNC. The formulation demonstrated significant ( p < .01) improvement in the activity of oxidative stress parameters and attenuation of neuroinflammatory markers. Based on the study findings, it was observed that formulating LNC of PPD would surmount the pharmacological constraints, improve the in vivo performance, and diminish the associated side effects.